The Making of Interactive Applications of Beginning Counting with Montessori Method for Kindergarten Students - Saputro, Andito Haryo; Maryono, Dwi; Sujana, Yudianto (Universitas Sebelas Maret, 2019)
This study aims to create an interactive application of beginning counting with the Montessori method that appropriate to apply as a learning media in Kindergarten. And also to find out the appropriateness of interactive application. The research method used in this research is Research and Development (R&D) and using the ADDIE development model. The development model is divided into 5 stages : (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. In the development stage, the RAD (Rapid Application Development) method is used. The interview method, literature method, and instrument method are used in collecting data. Further, interactive application validated or assessed by media expert and material expert. The results showed that the interactive application of beginning counting with the Montessori method successfully created. The application divided into 3 parts : (1) Knowing numbers, (2) Sorting numbers, and (3) Counting with numbers. Based on the results of the validation of the interactive application, the percentage of interactive application appropriateness were obtained 96.6% by material expert, and 94.7% by media expert. This shows that the interactive application that has been developed can be used as learning resources or learning media of beginning counting.